Efektivitas Pelaksanaan Hukuman Penahanan bagi Anggota Militer yang Melakukan Pelanggaran Disiplin Militer di Polisi Militer Angkatan Laut Lantamal V Surabaya - Syahrul Hafiidz Syam (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
In a country, elements of the field are needed to maintain unity and integrity in the country, one of which is the military. In Indonesia, the military element that maintains the sovereignty of the Republic of Indonesia is the Indonesian National Army (TNI). TNI soldier is formed through an educational process so that a soldier can carry out his duties properly according to the tasks given, both in combat and outside combat. But in the military area, which should be free from bad and despicable actions or behavior, in reality, TNI members are also ordinary people who cannot be separated from mistakes. It is possible for a soldier to disobey his superiors, or to commit a crime or violation that is detrimental to both the individual and the unit. This study aims to determine the effectiveness of law enforcement military discipline in the Military Police Lantamal V Surabaya and the imposition of penalties if there are members of the military who violate military discipline. This research uses empirical juridical research. Methods of data collection is done by means of interviews and literature studies. The results showed that there were still members of the military who violated military discipline. The data analysis technique in this study used qualitative data analysis. There are 5 (five) factors of legal effectiveness, namely the legal factor itself, law enforcement factors, facilities that support law enforcement, community factors, and cultural factors.